Augmented behavioral medicine competencies in physical therapy students' clinical reasoning with a targeted curriculum: a final-semester cohort-comparison study. (2nd December 2022) - Elvén, Maria; Dean, Elizabeth; Söderlund, Anne
ABSTRACT: Background: Knowledge regarding the impact of curricula with behavioral medicine content and competencies (BMCC) on physical therapy (PT) students' clinical reasoning skills is lacking. Objectives: The primary objective was to compare the clinical reasoning skills, focusing on clients' behavioral change, of entry-level PT students with or without BMCC in their curricula. The secondary objective was to compare students' attitudes and beliefs in a biomedical and biopsychosocial practice orientation. Methods: Swedish final-semester PT students (n = 151) completed the Reasoning 4 Change (R4C) instrument and the Pain Attitudes and Beliefs Scale for Physiotherapists. A blueprint was used for curricular categorization. The independent t-test was used. Results: Students attending programs with BMCC curricula (n = 61) had superior scores compared with students without BMCC curricula (n = 90) in the following R4C variables, all of which were related to clinical reasoning focused on behavioral change: Knowledge, Cognition, Self-efficacy, Input from the client, Functional behavioral analysis, and Strategies for behavioral change. Students who did not receive BMCC curricula scored higher in the R4C contextual factors and reported a greater biomedical practice orientation than students receiving BMCC curricula. There was no difference in the biopsychosocial practice orientation between groups. Conclusions: Our findings support the benefit of structured entry-level PT curricula with BMCC on final-semester students' clinical reasoning skills focused on behavioral change and their level of biomedical practice orientation. Further, our findings elucidated educational opportunities to augment students' self-efficacy and strengthen their behavioral competencies in clinical reasoning. For the generalizability of the results further research in other contexts is needed.